Socioeconomic contention and post-revolutionary political change in Egypt and Tunisia: a research agenda - Weipert-Fenner, Irene; Wolff, Jonas (2015)
Abstract: This working paper outlines a research agenda that aims at studying the dynamics and consequences of socioeconomic contention during the current processes of political transformation in the Middle East and North Africa (MENA) region from a comparative perspective that includes an interregional comparison with South America. In doing so, the authors review the state of research on socioeconomic protests in the MENA region, sketch an overall analytical framework and critically discuss the contentious politics approach on which this framework draws on. Finally, the paper presents a multilateral research project that has precisely set out to analyze to what extent and how socioeconomic contention shapes the ongoing process of political transformation in post-revolutionary Egypt and Tunisia